Congenital and Blood Transfusion Transmission of Chagas Disease: A Framework Using Mathematical Modeling. (1st November 2018) - Ramalho, Edneide; Albuquerque, Jones; Cristino, Cláudio; Lorena, Virginia; Gómez i Prat, Jordi; Prats, Clara; López, Daniel
Abstract : Chagas disease or American trypanosomiasis is an important health problem in Latin America. Due to the mobility of Latin American population around the world, countries without vector presence started to report disease cases. We developed a deterministic compartmental model in order to gain insights into the disease dynamics in a scenario without vector presence, considering congenital transmission and transmission by blood transfusion. The model was used to evaluate the epidemiological effect of control measures. It was applied to demographic data from Spain and sensitivity analysis was performed on model parameters associated with control strategies.